Perancangan Aplikasi Enkripsi Pada File Teks Menggunakan Algoritma Spritz - Syariah Kabeaken; Imam Saputra (STMIK Budi Darma, 2020)
The security of a file is a matter of concern in maintaining the confidentiality of information, especially those containing information that only the authorized parties may know about. Sending files or information without security will risk tapping and the information contained therein, can be easily known by unauthorized parties. One important thing in maintaining the confidentiality and security of files is the encryption process. Then based on techniques in cryptography, one of the methods that will be used in securing text files with the Spritz algorithm. Modern cryptography is more trusted by scientists than classical cryptography because it has a good level of security. Classical cryptography only does randomization from A-Z while modern cryptography operates in bit mode. The modern algorithm used is the Spritz algorithm. The Spritz algorithm is a variant of the RC4 algorithm, the security level of the Spritz algorithm is better than RC4